Pendampingan Pemasaran Produk Pada Usaha Roti Home Made - Paulina Rosna Dewi Redjo; Marce Sherly Kase; Anggelina Delfiana Klau; Desmon Redikson Manane (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The community service activities carried out are in the form of assistance for MSMEs "Home Made Bread Business" in terms of promotion and marketing of "Home Made Bread" products through social media such as WhatsApp, Instagram and Facebook. This assistance is intended to further introduce the product to consumers and expand the marketing area through the role of social media.